Emotional Intelligence and Workload Against Employee Burnout in the Review Human Management Perspective (Study on Employees of PT Indofood CBP Success Makmur Tbk Lampung) - Asri Suryani; Zulaikah Zulaikah; Weny Rosilawati (Universitas KH. Abdul Chalim Mojokerto, 2026)
Burnout is a condition of physical, emotional, and mental exhaustion due to prolonged work pressure. This study aims to analyze the effect of emotional intelligence and workload on employee burnout viewed from the perspective of human management on employees of PT Indofood CBP Sukses Makmur Tbk Lampung. This study uses quantitative methods with a descriptive approach. The study population was 203 employees, with a sample of 135 respondents determined using Slovin formula and purposive sampling technique. Data were collected through questionnaires and analyzed using SEM-PLS method with the help of SmartPLS software. The results showed that partially emotional intelligence had no significant effect on burnout, while workload had a positive and significant effect on employee burnout. Simultaneously, emotional intelligence and workload were only able to explain 27.9% of the variation in burnout, while the rest were influenced by other factors outside the research model. In the perspective of human management, these findings affirm the importance of fair and humane management of workload in order to maintain the physical, emotional and spiritual balance of employees.